SCARS AND KELOIDS: A COMPREHENSIVE REVIEW OF CURRENT TREATMENT MODALITIES - Jan Drzymała; Magdalena Rosiewicz; Karolina Bieńkowska; Anita Janda; Sylwia Bartolik; Marcin Durowicz; Iwona Górnicka; Aleksandra Pastuszek; Urszula Kierepka; Radosław Pastuszek (International Journal of Innovative Technologies in Social Science, 2025)
A skin scar is a result of the healing process of skin trauma. It can occur as a proper structure or as an abnormal growth, such as a hypertrophic scar and a keloid. Scar differs in surface, location, impact on other structures, and cosmetic view. Abnormal hypertrophic scar increases the risk of further irritation, scarring, disturbs the natural barrier, decreases in cosmetic view, and impacts daily life. There are different types of treatment for an excessive scar that can be applied in different cases. The steroid tapes, steroid injections, surgery, post-surgical radiation, dry needling, silicone materials, laser therapy, cryotherapy, massage, ACE inhibitors, and fat grafting.